Community-Based Tourism Development: A Qualitative Analysis of Ninh Binh (Vietnam) Local Stakeholders' Perspectives and Engagement - Nguyen, Tram (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
This study investigates the dynamics of community-based tourism in the culturally and naturally rich context of Ninh Binh. Utilizing sustainable tourism literature and qualitative methods such as observation and semi-structured interviews, the study aims to uncover the nuanced interplay between tourism development and local communities. Anticipating insights into the impact on residents' lives, livelihood changes, and challenges in local skills and knowledge, the research envisions providing practical implications for policymakers, tourism practitioners, and community members involved in community-based tourism initiatives. Positioned as a foundational resource, the study aspires to contribute to the global discourse on sustainable tourism, inspiring future research initiatives and fostering active community involvement in tourism development, not only in Ninh Binh but also in diverse regions aspiring to embrace sustainable and community-centered tourism approaches.